Upaya Peningkatan Pendapatan Melalui Orientasi Kewirausahaan Pada Usaha Kerajinan Anyaman Bambu Desa Tigawasa - Putu Pranjani Mahantari; Ni Luh Sri Kasih (ARTHA SATYA DHARMA, 2021)
This research is a qualitative study to examine the application of entrepreneurial orientation in the bamboo weaving handicraft business in Tigawasa Village. The focus of this research is to explain the application of entrepreneurial orientation in the bamboo weaving handicraft business in order to maintain the continuity of the bamboo woven handicraft business so that it can increase the income from the woven bamboo handicraft industry sector. The purpose of this study is to provide conclusions about the application of entrepreneurial orientation and the benefits obtained by applying entrepreneurial orientation. This research uses a qualitative approach with a case study method, the data analyzed is the result of interviews with woven bamboo handicraft business owners, consumers and the community of Tigawasa Village. The results showed that the application of entrepreneurial orientation through the application of innovation, risk taking and proactivity was effective. Because in the application of entrepreneurial orientation can improve company performance in achieving company goals.